Eine Analyse des Credit Spreads und seiner Komponenten als Grundlage für Hedge Strategien mit Kreditderivaten - Julia Krones; Heinz Cremers (Frankfurt School of Finance & Management, 2012)
– In almost every financial market crisis we can observe widening credit spreads, especially in the last years during the subprime and sovereign debt crisis. But what exactly drives the credit spread? This paper will outline static components, i.e. default risk, liquidity, risk and the relative attractiveness of government bonds. Afterwards we will shed some light on the dynamic components that underlie the changes in static components. Dynamic components comprise the economic situation, a market component, interest rates, term structure, time to maturity and credit rating migration. In the second part, this paper aims to provide an insight on how the risk contained in the credit spread can be hedged appropriately. This includes the definition of an appropriate hedge and how diversification influences the riskiness of credit portfolios. For single-name credit and market component risk the applicability of CDS will be examined. However, iTraxx Index Swaps are considered to be the superior instrument regarding hedging systematic market component risk on single-name and portfolio level. Finally, an excursus will investigate ways to extract default probabilities from credit spreads.
Keywords: G11; G12; G24; G32; 330; Credit Spreads; static credit spread components; dynamic credit spread components; active credit portfolio management; Credit Default Swaps (CDS); iTraxx; iTraxx Index Swaps; Credit risk diversification